Rise in temperature increases growth and yield of Manihot sp. plants (Research, Society and Development, 2022)
The selection of native forage species with yield potential under climate change scenarios can strengthen resilience of the Brazilian semiarid region. This study aimed to evaluate the effect of increasing temperature on growth and morphological and yield responses of plants of the genus Manihot. The experimental design was completely randomized in a 2×9 factorial arrangement (two temperature regimes and nine genotypes). The increase in temperature promoted higher plant dry mass (PDM) for genotypes A:24, A:79, A:102, A:EL, and A:GO during establishment. The percentage of leaves was reduced with the highest temperatures in the establishment, except for genotypes A:20, A:21, and A:GO. The increase in temperature during regrowth increased leaf dry mass (LDM) and reduced the leaf to stem ratio, except for A:24, A:79, and A:102, which presented similar values at both temperatures. Species of the genus Manihot respond differently to the 4.8 °C increase in air temperature. The increase in temperature shows a positive impact on the biomass production of species of this genus.